Internet addiction and relationships with depression, anxiety, stress and academic performance among Egypt pharmacy students: a cross-sectional designed study - Moustafa Sayed; Christina Medhat Naiim; Marina Aboelsaad; Michael Kamal Ibrahim (BMC, 2022)
Abstract Background and Aims Pharmacy students represent the future of healthcare professionals and with daily use of the internet for different activities has made internet addiction (IA) of a growing concern. The main objectives of this study were to 1) assess internet addiction among pharmacy undergraduate students as well as factors associated with it; 2) assess the relationships between internet addiction and common mental disorders (depression, anxiety, and stress), in addition to academic performance and body mass index factors. Methods We utilized a cross-sectional questionnaire that was conducted among 808 students of Egypt university pharmacy students across the country. The surveys used included: Young Internet Addiction Test (YIAT) and the Depression Anxiety Stress Scales (DASS 21). Results YIAT average score was 44.75 (19.72%); prevalence rate of potential IA was 311 (38.5%) with no gender significant difference. We couldn't detect any type of correlation between potential IA and GPA. However, a robust correlation was found between internet addiction vs depression, anxiety and stress collectively. Conclusions Internet addiction is usually associated with mental related disorders thus it is of paramount important to identify it among students. Different therapeutic interventions could include management to IA and common psychological disorders such as depression, anxiety, and stress.